Fossil diversity and taphonomy of glacial and post-glacial lower paleozoic strata, NE Paraná Basin, Brazil - Zabini, Carolina; Denezine, Matheus; Rodrigues, Lívia C. da S.; Gonçalves, Lívio R. de O.; Adôrno, Rodrigo R.; Carmo, Dermeval do; Assine, Mário L. [UNESP] (Elsevier, 2021)
Unlike other South American basins, the boundary between Ordovician and Silurian in the Paraná Basin, Brazil, has yet to be studied in detail. This article reports the occurrence and taphonomic analysis of a fauna composed of the organophosphatic brachiopods Kosoidea australis and ?Palaeoglossa sp., the mollusks ?Paleoneilo sp. and ?Cuneamya sp., besides rynchonelliform brachiopods and the ostracods Harpabollia sp. and Satiellina paranaensis. This assemblage indicates a Hirnantian age for the top of the Iapó and the base of the Vila Maria formations, northeastern border of the Paraná Basin. Taphonomic signatures and facies associations point to a pro-glacial environment, at the transitional shoreface, represented by the last sedimentary facies of the Iapó Formation. The overlying transgressive strata represent the beginning of the Vila Maria Formation, in which fossils and lithofacies indicate predominant post-glacial conditions in an offshore setting. Two taphofacies were delineated. One features size- and type-selected fossils, deposited in rain-out facies originated from the melting glacier. The second, with autochthonous to parautochthonous fossils, represents a post-glacial offshore setting. The low faunal diversity points to marine connections between North and South African basins, and with South American basins.
Keywords: Bivalve mollusks; Hirnantian; Organophosphatic brachiopods; Ostracods; Taphofacies